Modified gefitinib conjugated Fe3O4 NPs for improved delivery of chemo drugs following an image-guided mechanistic study of inner vs. outer tumor uptake for the treatment of non-small cell lung cancer - Thangudu, Suresh; Tsai, Ching-Yi; Lin, Wei-Che; Su, Chia-Hao (Frontiers in Bioengineering and Biotechnology, 2023)
Gefitinib (GEF) is an FDA-approved anti-cancer drug for the first-line treatment of patients with metastatic non-small cell lung cancer (NSCLC). However, the efficacy of anticancer drugs is limited due to their non-specificity, lower accumulation at target sites, and systemic toxicity. Herein, we successfully synthesized a modified GEF (mGEF) drug and conjugated to Iron oxide nanoparticles (Fe3O4 NPs) for the treatment of NSCLC via magnetic resonance (MR) image-guided drug delivery. A traditional EDC coupling pathway uses mGEF to directly conjugate to Fe3O4 NPs to overcom the drug leakage issues. As a result, we found in vitro drug delivery on mGEF- Fe3O4 NPs exhibits excellent anticancer effects towards the PC9 cells selectively, with an estimated IC 50 value of 2.0 μM. Additionally, in vivo MRI and PET results demonstrate that the NPs could accumulate in tumor-specific regions with localized cell growth inhibition. Results also revealed that outer tumor region exhibiting a stronger contrast than the tinner tumor region which may due necrosis in inner tumor region. In vivo biodistribution further confirms Fe3O4 NPs are more biocompatible and are excreated after the treatment. Overall, we believe that this current strategy of drug modification combined with chemical conjugation on magnetic NPs will lead to improved cancer chemotherapy as well as understanding the tumor microenvironments for better therapeutic outcomes.